Computational haemodynamic analysis of left pulmonary artery angulation effects on pulmonary blood flow. (9th June 2016) - Zhang, Weimin; Liu, Jinlong; Yan, Qin; Liu, Jinfen; Hong, Haifa; Mao, Le
Abstract : OBJECTIVES: To study the effect of the angulation between the left pulmonary artery (LPA) and the main pulmonary artery on pulmonary haemodynamics. METHODS: A 3D model of patient-specific pulmonary artery (PA) was reconstructed as an original model. Four models with descendent LPA angulation equalled to 120°, 110°, 100° and 90°, were reconstructed by computer-aided design for the virtual simulation of the pulmonary flow under different surgical strategies. Computational fluid dynamics was introduced to calculate the pulmonary blood flow in five models. Streamlines, wall shear stress, energy loss and flow distribution ratio were calculated and compared to determine the better haemodynamics in the pulmonary artery. RESULTS: Vortices were formed at the lower wall of the opening of right PA and LPA in models with LPA angles equal to or less than 100° (Models 3 and 4). Relative high wall shear stress areas at the lateral and lower wall of LPA opening had an ascendant tendency as the angle declined. Decreased flow distribution ratio to left lung (original model: 0.58, Model 1: 0.63, Model 2: 0.586, Model 3: 0.564, Model 4: 0.55) and increased energy loss (original model: 385.2 mV, Model 1: 239.4 mV, Model 2: 384.3 mV, Model 3: 430.9 mV, Model 4: 439.8 mV) in a cardiac cycle were noted as the angle reduced. CONCLUSIONS: Acute LPA angulation is associated with adverse haemodynamic performance. This should be particularly addressed during the reconstruction of pulmonary artery in the repair of tetralogy of Fallot.